Dietary acid load is associated with primary osteoporosis in postmenopausal women aged 50–65 years: A cross‐sectional study. Issue 2 (13th October 2022) - Farshbaf‐Khalili, Azizeh; Ostadrahimi, Alireza; Heris, Javad Ahmadian; Sarrafi, Somayyeh; Mohammadisima, Neda
Abstract: This study aimed to investigate the association between dietary acid load (DAL) and primary osteoporosis. This was a cross‐sectional study. Among 850 randomly selected postmenopausal women aged 50–65 years, 232 women consisted of 124 women with normal bone mineral density (BMD) and 108 with primary osteoporosis were selected after examining the eligibility criteria. Demographic characteristics, anthropometric indices, and physical activity were collected through questionnaires. Osteoporosis was diagnosed using the dual‐energy X‐ray absorptiometry method. DAL was assessed by a valid and reliable semiquantitative food frequency questionnaire during the last year. Independent t ‐test, Mann–Whitney, Chi‐square, and adjusted binary logistic regression were used for data analysis through SPSS/24. There were significant differences between the two groups in terms of age, body mass index (BMI), number of deliveries, and years after menopause ( p < .05). The mean (standard deviation (SD)) potential renal acid load (PRAL) and net endogenous acid production (NEAP) were higher in postmenopausal women with osteoporosis than those with normal BMD (PRAL: −13.1 ± 11.1 mEq/day vs. −10.8 ± 12.7 mEq/day; NEAP: 29.5 ± 8.5 mEq/day vs. 31.2 ± 9.2 mEq/day). The mean consumption of potassium, magnesium, and calcium in the osteoporosis group was significantly lower than in the other group ( p < .05). There were significant associations between osteoporosis with PRAL (odds ratio (OR) = 1.030; 95% confidence interval (CI): 1.001 to 1.060, p = .027) and NEAP scores (OR = 1.041; 95% CI: 1.003 to 1.081, p = .037). The odds of osteoporosis increased by 3% following one unit increase in PRAL score. Similarly, it increased by 4% with increasing NEAP score up to one unit. Therefore, dietary patterns that produce high DAL can have a detrimental effect on bone health. Abstract : Some observational studies and meta‐analyses dispute the claim that acid loads generally have a detrimental effect on bone. Due to inconsistencies in the results of previous studies and the lack of sufficient evidence regarding dietary acid load (DAL) and osteoporosis in women in the early postmenopausal ages, critical ages for bone loss due to a sudden drop in estrogen level, this study as the first one in Iran aimed to investigate the relationship between DAL (included potential acid renal load and net endogenous acid production) and osteoporosis in these women.